POTENSI PEMANGSAAN PREDATOR REDUVIIDAE (Rhinocoris fuscipes F.) TERHADAP Helicovepa spp - Sanjaya, Yayan (Jurnal Pengajaran MIPA, 2005)
In agriculture environment needed a support the crop to increase product and  environment support to  improvement of a product which  done holisticly. The pesticide Application minimize  still  has a priority, replace with insect entomofagus, mikroorganisme entomopatogen and parasitoid  for environment stabiliy. Natural Enemy population  including predator have the very specific and unique ability for the interaction of with the prey,  population of  host  and it can as regulator. The methode used by survey to farm area in Semudang and rear it at lab and also observe the yhe prey behaviour. The result show that the predator (Rhinocoris fuscipes F.) is needed H. armigera as. a prey abouat 5  or more for each day. The Rhinocoris fuscipes F.  Rhinocoris fuscipes F. has an active behaviour to prey H. armigera.